Colonial Architecture Identification Of Uleebalang House In Aceh Through A Typological Approach (Case Study: Uleebalang House In Kec. Muara Batu, Gandapura And Peusangan) - Sarah Nurfajar; Armelia Dafrina; Yenny Novianty (LPPM Universitas Malikussaleh, 2022)
Colonial architecture in Indonesia is a unique cultural form, this is not found anywhere else or in countries that were once occupied by the Dutch colonialists, because colonial architecture that developed in Indonesia contained a blend of cultures between the Dutch and Indonesians with a wide variety of building designs. Colonial architecture has the peculiarities of buildings that are able to adapt to local conditions and the local climate of each design. One of the colonial heritage architecture of the Netherlands is a house, especially in Aceh Province. These houses have the same concept, namely the concept of colonial architecture, but each building also has a different shape, such as different shapes in plans, facades and elements. Research on the Uleebalang house is important to do in order to maintain and maintain the historical value that once existed so that it can be preserved for the next generation. This study took three samples of houses, one of which is located in Kab. North Aceh (Uleebalang Krueng Mane's house) and two in Kab. Bireuen (Uleebalang Geurugok's house and Uleebalang Peusangan's house). This research concludes that there are many similarities between the Uleebalang Krueng Mane house and the Uleebalang Geurugok house, while the Uleebalang Peusangan house has differences in the floor plan and several other elements.